KANDUNGAN GIZI DAN DAYA TERIMA COKELAT BATANG DAUN KELOR - Kartika; Lena Ahdiyani Hayati; Ririn Purwati (Jurnal Fakultas Teknik Kuningan, 2023)
Moringa leaves (Moringa oleifera) is a plant that has many properties and benefits for human health. Processing of Moringa leaves in Indonesia has not been widely carried out, this is due to the lack of public knowledge of the benefits of Moringa leaves. For this reason, there is a need for food diversification of Moringa leaves. One effort that can be done is to make functional chocolate bars by adding moringa leaf powder which can have a positive effect on the health of the body. One of the ways to diversify this type of food is by processing Moringa leaves into brown moringa leaf stems. This study aims to look at the nutritional content and acceptability of Moringa chocolate stems. The research method was divided into four stages: designing a chocolate formula with Moringa leaf powder, making Moringa chocolate, hedonic testing of the selected formula, and analyzing the nutritional value of Moringa chocolate. The experimental design used in this study was a one-factor completely randomized design (CRD) consisting of three levels, namely 0.01%, 0.02% and 0.03%. The results showed that chocolate with the addition of 0.01% moringa leaf powder was the most preferred by the panelists. The nutritional content of chocolate with the selected formula is 0.83% moisture content, 0.67% ash content, 2.14% protein content, 35.80% fat content, and 60.56% carbohydrates.